Thermal decomposition dynamics study and products analysis of different fibers for wrapping paper - Wei, Haiying; Shen, Xiaochen; Zhao, Guoliang; You, Min; Zhou, Lidong; Wu, Kai; Zhu, Chengwen; Zhu, Wenyuan; Huang, Yang; Ma, Mengtao (Frontiers in Materials, 2025)
The pyrolysis properties of wrapping paper fiber raw materials are of great significance for burning rate and the taste of cigarettes, therefore, it is essential to study the thermal decomposition dynamics of wrapping paper fibers. This paper investigated the pyrolysis characteristics and patterns of different fibers (softwood pulp, hardwood pulp, and non-wood pulp) used in wrapping paper using a thermogravimetric analyzer. The key parameters of their TG curves were determined, and the kinetic mechanism function of pulp pyrolysis was inferred based on the TG curve. The apparent activation energy (E) and pre-exponential factor (A) for the pyrolysis of each pulp were calculated, and the relationship between key pyrolysis parameters and apparent activation energy was identified. The pyrolysis products of the samples at different decomposition temperatures were studied using pyrolysis-gas chromatography-mass spectrometry. The results indicated that the correlation between apparent activation energy E and Tmax is more significant. As the pyrolysis temperature increases, the types of pyrolysis products increase to more than 17. This study provides a theoretical support for the selection of pulp in the production of wrapping paper.